2018
DOI: 10.1093/jjco/hyy129
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of abiraterone acetate plus prednisone in Japanese patients with newly diagnosed, metastatic hormone-naïve prostate cancer: a subgroup analysis of LATITUDE, a randomized, double-blind, placebo-controlled, Phase 3 study

Abstract: Abiraterone acetate plus prednisone in addition to androgen-deprivation therapy (ADT) was efficacious versus ADT alone in Japanese men with metastatic hormone-naïve prostate cancer. No new safety concerns were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 40 publications
9
46
0
Order By: Relevance
“…In particular, with respect to response to initial ADT, our cohort showed longer PFS (12.3 months) than that of the CHAARTED study cohort (8.6 months) 7,13 . Due to the high survival rate, no OS benefit was discernable in the Japanese subgroup analysis of the LATITUDE study 12 . A racial difference may thus exist in response to hormonal therapy.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In particular, with respect to response to initial ADT, our cohort showed longer PFS (12.3 months) than that of the CHAARTED study cohort (8.6 months) 7,13 . Due to the high survival rate, no OS benefit was discernable in the Japanese subgroup analysis of the LATITUDE study 12 . A racial difference may thus exist in response to hormonal therapy.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, a meta‐analysis revealed that the administration of docetaxel and abiraterone acetate combination with ADT did not improve OS compared with ADT alone in patients >70 years old 16 . Patients with de novo metastatic PCa tend to be relatively old at diagnosis (median age was 73 years in our study and 70 years in a Japanese prospective cohort study) 12 . Considering these issues, selection should be more discussed to those patients requiring potent upfront treatment in mCNPC.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Some retrospective studies have found greater OS in Japanese men with de novo mHSPC, compared with other races. Recently, a subgroup analysis of the LATITUDE trial in Japanese patients also showed that the progression‐free survival in the Japanese subgroup was superior to that of the overall population, in both the androgen deprivation therapy plus abiraterone and androgen deprivation therapy only arms . Differences in ethnicities and treatment environments might influence hormonal therapy treatment outcomes; however, the precise mechanisms that affect these differences remain unknown, and further genetic analyses are required to elucidate these issues in the future.…”
mentioning
confidence: 99%